Marginalized primary education in Saponda Village, Soropia District, Konawe Regency: Study of socioeconomic and transportation limitations - I Ketut Suardika; La Rabani; Muliha Halim (Sang Pencerah: Jurnal Ilmiah Universitas Muhammadiyah Buton, 2020)
This study proposes to contribute information in the form of a description of the limitations of economic and transport affect the marginality of primary education. The research is a qualitative descriptive study with the location of the study in Saponda Village Soropia District Konawe Regency. The collection of data obtained through interviews, observation and documentation. The data used are primary data obtained directly through the interview process, interviews and secondary data obtained through the village profile Saponda. The results of the study found that the form of economic marginalization community is due to the lack of government attention in efforts to improve the welfare of the community, mostly as traditional small fishermen. Moreover, limited transportation has an impact on the mobility of teachers to Saponda also limited. Besides, the public desire to deliver his son to obtain a decent education outside the village Saponda also limited. Therefore, political governments need to pay more attention to the socio-economy and transportation, especially the Bajo tribe community.